Risk factors for measles virus infection and susceptibility in persons aged 15 years and older in China: A multi-site case-control study, 2012–2013. Issue 16 (3rd April 2020) - Ma, Chao; Hao, Lixin; Rodewald, Lance; An, Qian; Wannemuehler, Kathleen A.; Su, Qiru; An, Zhijie; Quick, Linda; Liu, Yuanbao; Yan, Rui; Liu, Xiaodong; Zhang, Yanyang; et al.
Highlights: Hospital exposure was associated strongly with measles in susceptible Chinese adults. Approximately 20% to 40% of adult measles cases may have been acquired in hospitals. Strengthening infection control practices is needed to reduce risk of measles. Measles susceptibility was associated with occupation and lack of interest in SIAs. Serological testing of controls allowed identification of transmission risk factors. Abstract: Introduction: Endemic measles persists in China, despite >95% reported coverage of two measles-containing vaccine doses and nationwide campaign that vaccinated >100 million children in 2010. An increasing proportion of infections now occur among adults and there is concern that persistent susceptibility in adults is an obstacle to measles elimination in China. We performed a case-control study in six Chinese provinces between January 2012 to June 2013 to identify risk factors for measles virus infection and susceptibility among adults. Methods: Persons ≥15 years old with laboratory-confirmed measles were age and neighborhood matched with three controls. Controls had blood specimens collected to determine their measles IgG serostatus. We interviewed case-patients and controls about potential risk factors for measles virus infection and susceptibility. Unadjusted and adjusted matched odds ratios and 95% confidence intervals (CIs) were calculated via conditional logistic regression. We calculated attributable fractions for infection for risk factors that could be interpreted as causal. Results: 899 cases and 2498 controls were enrolled. Among controls, 165 (6.6%) were seronegative for measles IgG indicating persistent susceptibility to infection. In multivariable analysis, hospital visit and travel outside the prefecture in the prior 1–3 weeks were significant risk factors for measles virus infection. Occupation and reluctance to accept measles vaccination were significant risk factors for measles susceptibility. The calculated attributable fraction of measles cases from hospital visitation was 28.6% (95% CI: 20.6–38.8%). Conclusions: Exposure to a healthcare facility was the largest risk factor for measles virus infection in adults in China. Improved adherence to hospital infection control practices could reduce risk of ongoing measles virus transmission and increase the likelihood of achieving and sustaining measles elimination in China. The use of control groups stratified by serological status identified distinct risk factors for measles virus infection and susceptibility among adults.